Theoretical and Practical Analysis on the Quality of Active Subject of the Corruption Offenses of the Bank Clerk in the Sense of His Assimilation to the Civil Servant - Moise, Gheorghe (Journal of Legal Studies, 2022)
The quality of the active subject of the bribery offense that can be retained to the bank clerk is based on the logical-legal argument that the duties he performs are subject to the control of a public authority, which recognizes that at least in terms of the importance of this activity. type of official we place ourselves in an area of authority and public interest. If at the beginning the legislator placed the bank clerk among the private persons who in terms of activities were likely to acquire the status of active subject of the crime of bribery, then he returned and placed him among the category of employees assimilated to civil servants. This much stronger link between the activity of this official, the purpose of his duties and the subordination of his own activity to a public authority, was the new argument underlying the current criminal regulations, which recognizes the quality of active subject of the offense of bribing the bank clerk.